Rethinking Flow Beyond Control An Outreach Legal Essay - Bergé, Jean-Sylvestre (Confluence des droits, 2021)
In his 1978 lecture at the Collège de France on the theme of "Security, territory and population", Michel Foucault established a link between "circulation", "security" and "space". He depicted the approach to circulation in the 17th and 18th centuries, based on legal tools such as international agreements and national or local regulations, as the expression of a desire to secure flows in the different spaces (maritime and terrestrial). The objective of this legal essay, intended for a broad readership, is to counter this analysis by arguing that, for a certain number of major forms of circulation (release of greenhouse gases, spread of products and organisms of all kinds, pandemics, dissemination of information, movement of persons, data, capital, waste, etc.), mankind is living with an illusion of control. The question is no longer who controls what, but rather who is suffering the loss of control? To answer this question, we must rethink our traditional models of circulation and control. All sorts of a priori approaches to circulation can be discussed (magical, liberal, social, ontological, fundamental, modal). As for control, we must recognise that it is perennially exercised in an environment full of holes.